Melanoma Cell Expression of CD200 Inhibits Tumor Formation and Lung Metastasis via Inhibition of Myeloid Cell Functions - Talebian, Fatemeh; Liu, Jin-Qing; Liu, Zhenzhen; Khattabi, Mazin; He, Yukai; Ganju, Ramesh; Bai, Xue-Feng (PLOS ONE, 2012)
CD200 is a cell surface glycoprotein that functions through engaging CD200 receptor on cells of the myeloid lineage and inhibits their functions. Expression of CD200 has been implicated in a variety of human cancer cells including melanoma cells and has been thought to play a protumor role. To investigate the role of cancer cell expression of CD200 in tumor formation and metastasis, we generated CD200-positive and CD200-negative B16 melanoma cells. Subcutaneous injection of CD200-positive B16 melanoma cells inhibited tumor formation and growth in C57BL/6 mice but not in Rag1−/−C57BL/6 mice. However, i.v. injection of CD200-positive B16 melanoma cells dramatically inhibited tumor foci formation in the lungs of both C57BL/6 and Rag1−/−C57BL6 mice. Flow cytometry analysis revealed higher expression of CD200R in Gr1+ myeloid cells in the lung than in peripheral myeloid cells. Depletion of Gr1+ cells or stimulation of CD200R with an agonistic antibody in vivo dramatically inhibited tumor foci formation in the lungs. In addition, treatment with tumor antigen specific CD4 or CD8 T cells or their combination yielded a survival advantage for CD200 positive tumor bearing mice over mice bearing CD200-negative tumors. Taken together, we have revealed a novel role for CD200-CD200R interaction in inhibiting tumor formation and metastasis. Targeting CD200R may represent a novel approach for cancer immunotherapy.